Measuring the Impact of the Central Bank's Financial Position Statement on the Money Supply – Using the NARDL Standard Model - Jarry, Widyan Waheeb; Dagher, Mahmoud Mohamed (Journal of Cultural Analysis and Social Change, 2025)
The analysis of the Central Bank's financial position statement, and the changes in its items in the aspects of assets and liabilities, is an essential entry point to understand the nature of the Central Bank's activity, its monetary policy directions, and the extent of its powers in performing its main functions. ) to measure the equilibrium and causal relationships between the variables of the list, represented by net foreign assets, net domestic assets, and the monetary base, and their effect on the money supply (M2) in the short and long term, and the stability of the money supply function was also tested to verify the stability of the relationship during the study period.The importance of this research is highlighted in its connection between the structural and qualitative analysis of the statement of the financial position of the Central Bank and the quantitative analysis of the behavior of the money supply, which contributes to deepening the understanding of the mechanism of the influence of the components of the list on monetary variables and in the formulation of macroeconomic policy.